The Effects of Magnesium Borate Whiskers on the Mechanical Performance of Oil Well Cement - Xianshu Gao; Ping Zhou; Xiaoliang Qin; Zhaijun Wen; Jing Wang; Hao Wang; Ming Li; Jia Zhuang; Chengxin Li (Advances in Materials Science and Engineering)
Quasi-brittle behaviors of cement-based material can be reinforced through diverse methods due to its unique multiscale features. Among them, reinforcing agents are the most direct and effective means, such as slag, metakaolin, and fly ash. These materials can improve the performance of cement stone to a certain extent, but their chemical composition is still mainly silica, which does not in essence change the defects of cement. Therefore, in this experiment, magnesium borate whisker (Mg2B2O5) was used as reinforcer of 90°C class G oil well cement and magnesium borate whisker reinforced cement-based material (MBWRC) was prepared. On the one hand, the performance of mechanical strength was controlled, and the resistance to compression, traction, and bending was included. Furthermore, static stress-strain behaviors analysis and toughness behaviors analysis (dynamic multicycle loading test) were further conducted. Second, mercury intrusion porosimetry (MIP) and scanning electron microscope (SEM) were used to test the characteristics of pores and interfaces of cement-based materials. Through multiscale microstructure analysis, MBWRC was found to have excellent 90°C mechanical performances when compared to control sample’s, for which tensile strength increased to 235% of controlled sample’s, and flexural strength increased to 130%, plus a healthy developed compressive performance, and MBWRC showed much denser pore structure, in which harmless micropore increased from 13.3% to 14.40%, porosity decreased from 17.01% to 16.20%, and permeability decreased from 0.2533% to 0.0205%. Furthermore, MBWRC showed resistance capability to mechanical loading, which can be attributed to the formation of denser pore structure and more excellent mechanical performance.